Mapping of a Novel Autosomal Recessive Nonsyndromic Deafness Locus (DFNB46) to Chromosome 18p11.32-p11.31 - Mir, Asif (2005)
Hereditary nonsyndromic deafness (NSD) is extremely heterogeneous. Autosomal recessive (AR) forms account for ~75% of genetic cases. To date, over 40 ARNSD loci have been mapped. A novel locus (DFNB46) for ARNSD was mapped to chromosome 18p11.32-p11.31 in a five-generation Pakistani family. A 10 cM genome-wide scan and fine mapping was carried out using microsatellite markers. A maximum multipoint LOD score of 3.8 was obtained at two markers, D18S481 and D18S1370. The three-unit support interval is flanked by markers D18S59 and D18S391, corresponds to a 17.6 cM region according to the decode genetic map and spans 5.8 Mb on the sequence-based physical map.